BIOMASSA SESAAT SUMBER DAYA PERIKANAN UNDUR-UNDUR LAUT (CRUSTACEA: DECAPODA: HIPPIDAE) DI PANTAI BERPASIR CILACAP DAN KEBUMEN, JAWA TENGAH - Ali Mahsar; Yusli Wardiatno (Bogor Agricultural University, 2016)
ABSTRACTMole crab is a benthic animal that live buried in sandy beach in the intertidal area. Mole crab has an important ecological role and also has economic value. The sandy beach in south of Cilacap and Kebumen is mole crab’s habitat. Mole crab exploitation in these areas has been increasing for consumption demand. To determine the significant role of the mole crab in the provision of nutritious food, it is necessary to estimate the potential of mole crab biomass. This study aims to determine standing biomass of the mole crab in Kebumen and Cilacap sandy beaches. The specimen collection was conducted by sampling methods every month in March 2012 to February 2013 on Bocor beach, Kebumen and June 2013 to May 2014 on Bunton beach, Cilacap. The data processing was conducted by descriptive statistics methods. The results showed that standing biomass of mole crab family Hippidae, namely Emerita emeritus and Hippa adactyla, fluctuated between 102 and 508 kg on the Kebumen sandy beach, and between 1,811 and 4,671 kg on the Cilacap sandy beach. Standing biomass of E. emeritus fluctuated between 82 and 497 kg on the Kebumen sandy beach and between 1,462 and 3,560 kg on the Cilacap sandy beach.Standing biomass of H. adactyla fluctuated between 2 and 133 kg on the Kebumen sandy beach, and between 234 and 1,701 kg on the Cilacap sandy beach. The difference in standing biomass in each location was caused by the difference of sampling time and environment condition of research area. The economic value potential of the mole crab as fishery resources is discussed.Keywords: Emerita emeritus, Hippa adactyla, Hippidae, momentarily biomass,ABSTRAKUndur-undur laut adalah kelompok hewan bentik yang hidup mengubur di daerah intertidal bersusbtrat pasir. Undur-undur laut mempunyai peran ekologis penting dan juga bernilai ekonomis. Pantai berpasir selatan Cilacap dan Kebumen adalah habitat undur-undur laut. Penangkapan undur-undur laut di kedua wilayah tersebut makin meningkat untuk kebutuhan konsumsi. Untuk mengetahui peran undur-undur laut dalam mendukung penyediaan bahan pangan bergizi, perlu diketahui potensi biomassa undur-undur laut. Penelitian ini bertujuan untuk mengetahui biomassa sesaat undur-undur laut dan fluktuasinya di pantai berpasir Kabupaten Kebumen dan Cilacap. Pengumpulan spesimen undur-undur laut dilakukan dengan metode sampling setiap bulan pada Maret 2012 hingga Februari 2013 di pantai Bocor Kebumen dan pada Juni 2013 hingga Mei 2014 di pantai Bunton Cilacap. Pengolahan data dilakukan dengan metode statistik deskriptif. Hasil penelitian menunjukkan bahwa besaran biomassa sesaat (standing biomass) undur-undur laut famili Hippidae, yaitu Emerita emeritus dan Hippa adactyla, berfluktuasi antara 102 kg hingga 508 kg di pantai berpasir Kebumen, dan antara 1.811 kg hingga 4.671 kg di pantai berpasir Cilacap. Standing biomass E. emeritus berfluktuasi antara 82 kg hingga 497 kg di pantai berpasir Kebumen dan antara 1.462 kg hingga 3.560 kg di pantai berpasir Cilacap. Standing biomass H. adactylaberkisar antara 2 kg hingga 133 kg di pantai berpasir Kebumen, dan antara 234 kg hingga 1.701 kg di pantai berpasir Cilacap. Perbedaan besaran standing biomass di masing-masing lokasi dipengaruhi oleh perbedaan waktu pengumpulan data undur-undur laut dan perbedaan kondisi lingkungan lokasi penelitian. Potensi ekonomi sebagai sumber daya perikanan undur -undur laut juga dibahas dalam paper ini.Kata kunci: Emerita emeritus, Hippa adactyla, Hippidae, biomassa sesaat